Lambda Interferons: New Cytokines with Old Functions - Ole J. Hamming; Hans Henrik Gad; Søren Paludan; Rune Hartmann (MDPI AG, 2010)
Interferon lambda (IFN-λ) is a member of the class II cytokine family, and like the other members of this family, they are small helical proteins. Since their discovery significant efforts have been made to determine their role in innate and adaptive immunity. Their strong antiviral activity, both in vitro and in vivo, has firmly established their interferon status. However, in contrast to type I interferon, only a very limited subset of cells/tissues responds to interferon lambda. In addition to inducing an antiviral state in responsive cells, recent data suggest that IFN-l plays a role in shaping the adaptive immune response. However, the data is not in complete agreement regarding the effect of IFN-λ on the adaptive immune system. Recently IFN-l has entered clinical trials against hepatitis C Virus and IFN-l is a promising future therapeutic, against different viruses replicating in responsive tissues, like that of the airway epithelia. In this review we describe the knowledge acquired during the past six years about the structure and function of interferon lambda.